Dimensi Maqasid Syariah dalam Putusan Hakim Atas Perkara Cerai Gugat di Pengadilan Agama Jayapura (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
This study is intended to look at the dimensions of maqashid sharia in the judge's decision at the Jayapura Religious Court. This aspect of maqasid sharia is important to look at considering that so far there has often been an assumption that judges' decisions in religious courts in Indonesia do not take this aspect into account. This study is a normative-empirical legal study with the type of judicial case study. The data source for this research is the judge's decision at the Jayapura Religious Court number 297/Pdt.G/2021/PA.Jpr. This study shows that the judge's decision at the Jayapura Religious Court already contains maqashid sharia values from the perspective of Jasser Auda. This can be seen from the broad scope of the judge's considerations which not only look at the formal and administrative aspects, but also the systemic implications for the parties, so that the fact of a fight is not only seen as a fight, but also has a negative impact on the physical and mental health of the parties. Likewise, the judge saw the fact of negligence towards the husband's responsibilities in the scope of the life of his wife and children in the future.